2017
DOI: 10.1038/s41598-017-04212-8
|View full text |Cite
|
Sign up to set email alerts
|

The CpG-sites of the CBX3 ubiquitous chromatin opening element are critical structural determinants for the anti-silencing function

Abstract: Suppression of therapeutic transgene expression from retroviral gene therapy vectors by epigenetic defence mechanisms represents a problem that is particularly encountered in pluripotent stem cells (PSCs) and their differentiated progeny. Transgene expression in these cells, however, can be stabilised by CpG-rich ubiquitous chromatin opening elements (UCOEs). In this context we recently demonstrated profound anti-silencing properties for the small (679 bp) CBX3-UCO element and we now confirmed this observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Also in the context of lentiviral vectors, the MRP8 promoter shows a high abundance of repressive histone marks and low transgene expression in iPSC-derived myeloid cells 34 . The inclusion of insulators or ubiquitous chromatin opening elements (UCOE), such as the 1.8 kb element or a shortened CBX3 version, could help to overcome transgene silencing 21,[34][35][36] . Insulators are DNA sequences that block the spread of heterochromatin and thus protect against silencing and DNA methylation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Also in the context of lentiviral vectors, the MRP8 promoter shows a high abundance of repressive histone marks and low transgene expression in iPSC-derived myeloid cells 34 . The inclusion of insulators or ubiquitous chromatin opening elements (UCOE), such as the 1.8 kb element or a shortened CBX3 version, could help to overcome transgene silencing 21,[34][35][36] . Insulators are DNA sequences that block the spread of heterochromatin and thus protect against silencing and DNA methylation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Soon after, the 1.5 kb core region was identified, along with the discovery that a 1.2 kb sub-fragment of that element was equally effective in promoting stable expression (14,17). Since then, a variety of individual studies have found efficacy from variable lengths of the core sequence, but those additional truncations, up to 600 bp, have not been proven out further than the one specific application in each study (16,23,24). Thus, there remains a need for a single modular sequence under 1 kb that can predictably stabilize a broad diversity of gene expression constructs.…”
Section: Introductionmentioning
confidence: 99%
“…As a second strategy, we exploited targetable CHO cell lines to adjust the cassette design to the requirements of the particular integration sites. We focused on UCOEs since they have been shown to convey an open chromatin status that was also maintained upon differentiation of blood as well as pluripotent stem cells, thereby preventing the silencing of transgenes. Moreover, UCOEs have been shown to improve expression of various recombinant genes including antibodies. So far, however, UCOEs have been mainly characterized upon random chromosomal integration of the vectors, by comparing clones with UCOE-free and UCOE-supplemented vectors.…”
Section: Discussionmentioning
confidence: 99%
“…integration sites. We focused on UCOEs since they have been shown to convey an open chromatin status that was also maintained upon differentiation of blood71 as well as pluripotent72 stem cells, thereby preventing the silencing of transgenes. Moreover, UCOEs have been shown to improve expression of various recombinant genes including antibodies.73−76 So far, however, UCOEs have been mainly…”
mentioning
confidence: 99%